In vitro antiparasitic activity and chemical composition of the essential oil from Protium ovatum leaves (Burceraceae) - ESTEVAM,ELISÂNGELA B.B. (2017)
ABSTRACT Leishmaniasis and trypanosomiasis are globally widespread parasitic diseases which have been responsible for high mortality rates. Since drugs available for their treatment are highly hepatotoxic, nephrotoxic and cardiotoxic, adherence to therapy has been affected. Thus, the search for new, more effective and safer drugs for the treatment of these diseases is necessary. Natural products have stood out as an alternative to searching for new bioactive molecules with therapeutic potential. In this study, the chemical composition and antiparasitic activity of the essential oil from Protium ovatum leaves against trypomastigote forms of Trypanosoma cruzi and the promastigote forms of Leishmania amazonensis were evaluated. The essential oil was promising against trypomastigote forms of T. cruzi (IC50= 28.55 μg.mL-1) and L. amazonensis promastigotes (IC50 = 2.28 μg.mL-1). Eighteen chemical constituents were identified by Gas Chromatography coupled to Mass Spectrometry (GC-MS) in the essential oil, whose major constituents were spathulenol (17.6 %), caryophyllene oxide (16.4 %), β-caryophyllene (14.0 %) and myrcene (8.4 %). In addition, the essential oil from P. ovatum leaves had moderate cytotoxicity against LLCMK2 adherent epithelial cell at the concentration range under analysis (CC50 = 150.9 μg.mL-1). It should be highlighted that this is the first report of the chemical composition and anti-Trypanosoma cruzi and anti-Leishmania amazonensis activities of the essential oil from Protium ovatum leaves.